We Cannot Win the Access to Medicines Struggle Using the Same Thinking That Causes the Chronic Access Crisis - Gaëlle Krikorian; Els Torreele (Harvard FXB Center for Health and Human Rights, 2020)
The inequity in access to COVID-19 vaccines that we are witnessing today is yet another symptom of a pharmaceutical economy that is not fit for purpose. That it was possible to develop multiple COVID-19 vaccines in less than a year, while at the same time fostering extreme inequities, calls for transformative change in the health innovation and access ecosystem. Brought into the spotlight through the AIDS drugs access crisis, challenges in accessing lifesaving medicines and vaccines-because they are either not available or inaccessible due to excessive pricing-are being faced by people all over the world. To appreciate the underlying framing of current access discussions, it is important to understand past trends in global health policies and the thinking behind the institutions and mechanisms that were designed to solve access problems. Contrary to what might be expected, certain types of solutions intrinsically carry the conditions that enable scarcity, rationing, and inequity, and lead us away from ensuring the right to health. Analyzing the root causes of access problems and the political economy that allows them to persist and even become exacerbated is necessary to fix access inequities today and to design better solutions to ensure equitable access to health technologies in the future.